Efektivitas Penerapan Probio_Fmubb Terhadap Pertumbuhan Lele (Clarias Sp.) Pada KJA Kolam Tanah, Bangka Belitung - Emya Br Sitanggang; Baifa Baifa; Addela Amelia; Sudirman Adibrata; Yeyen Mardyani (Jurnal Akuakultur Sungai dan Danau, 2023)
Catfish feed added with probiotics can affect the growth and health of fish. This study aims to determine the effectiveness of applying Probio_FmUBB to catfish growth. The research was conducted from September to November 2022 for catfish (Clarias sp.) growing-out in the floating fish cages (KJA) owned by CV. Dua Agri Mandiri (CV. DAM) in Petaling Village, West Mendo District, Bangka Regency, Kepulauan Bangka Belitung Province. The sampling method used simple random sampling of catfish in two ponds, fed with probiotic and non-probiotic feed. The results showed that feeds with the addition of the probiotic Probio_FmUBB make differences in the weight and length growth of catfish, where the fish grew faster and heavier than catfish fed with non-probiotic feed. Both catfish groups in the initial phase both showed rapid growth and slowed down in the adult phase. The final measurement showed that catfish with probiotic feed had an average weight of 28.5 grams and an average length of 112.8 cm, while catfish with non-probiotic feed had an average weight of 26.64 grams and an average length of 108.4 cm. It is assumed that the application of Probio_FmUBB probiotics on feed works effectively compared to feed without probiotics. The digestibility showed that the feed with Probio_FmUBB is absorbed  into nutrients more efficiently by catfish. The water quality in the earthen-pond KJAs shows values that are not considerably different and is still acceptable in the water quality standard criteria for fish farming. The water does not smell, and it is assumed that the ammonia decay at the pond bottoms is not high.